Pembunuhan Terhadap Pencuri: Aspek Hukum Dan Keadilan Dalam Penegakan Hukum Pidana - P. Berutu, Sigar; Tysennerick Berley; Yoga Dharmawan, Aldy; Hakim Lubis, Andi (Universitas Kapuas, 2024)
This research examines the phenomenon of killings committed against thieves, particularly within the context of criminal law. The study aims to explore legal aspects associated with the act of killing thieves and analyze the justice factors in the enforcement of criminal law concerning such cases. The research methodology utilized both normative and empirical juridical approaches. Data were obtained through literature reviews from various legal sources and the analysis of cases occurring in society. This approach enables a comprehensive understanding of legal issues related to the killing of thieves. The research findings indicate that the practice of killing thieves raises complex moral and legal dilemmas. A review of laws and legal precedents reveals diverse perspectives related to these acts of killing.